Applications of Malaysia deposit insurance corporation (MDIC) to takaful operators: an analysis from the shariah advisors’ perspective - Abdullah, Nurdianawati Irwani (EBSCO Host, 2012)
The global takaful market is estimated by market analysts to reach a premium of U.S. $ 12.5 billion by 2015. Malaysia is considered the second largest takaful in the world with total asset of US$ 3.2 billion. One of the new innovations of takaful and insurance in Malaysia is Perbadanan Insurance Deposit Malaysia (PIDM) which is also known internationally as the Malaysia Deposit Insurance Corporation (MDIC). The role of MDIC is to provide protection to owners of takaful certificate and to ensure the stability and confidence in the market by protecting policy holder (takaful certificate). Therefore, this study investigates the extent to which MDIC is relevant to takaful operators. Personal interviews are carried out with shariah advisers of takaful operators to deduce the actual practice, the ideal role and to gain access to the field of MDIC and its implications in Malaysia. The findings of this research indicate that MDIC is relevant to takaful operators and part of the regulations that should be supported and encouraged. Furthermore, the study also found that shariah advisers suggest Wakalah bi ajr as an alternative of kafalah-bi al-ajr by shifting the scheme to tabarru‘ model. In addition, the study found that the contribution paid should be charged to the participants’ fund; this is because the protection provided by MDIC is for the fund that belongs to the participants and takaful operators deemed to be wakeel (agent) only.